A ففتھ جنریشن وار سیرت طیبہ کے تناظر میں تحقیقی جائزہ - Muhammad Attique; Manzoor Ahmed Al Azhari (Mujalla Islami Fikr-o-Tahzeeb (MIFT) / مجلہ اسلامی فکر و تہذیب, 2023)
The concept of fifth-generation warfare (5GW) is becoming increasingly relevant in modern times. Unlike traditional warfare, 5GW is fought in an unconventional manner using information warfare, propaganda, and cyber-attacks. The goal of 5GW is not to defeat the enemy militarily, but rather to destabilize their society psychologically and mentally through a long-term war that operates beyond geographical boundaries and limitations. In this context, there is a pressing need to raise awareness about the importance of fifth-generation warfare in the light of Islamic teachings. The Qur'an and Sunnah provide a framework for understanding the nature of warfare and the principles of defense. The Messenger of the Universe also demonstrated strategic foresight in his approach to warfare, which can serve as a guide for contemporary military leaders. Using a qualitative research methodology, the study analyzes the relevant literature, like; scholarly articles, books, and government reports on 5GW and Islamic teachings. The findings of the research suggest that 5GW poses a serious threat to the stability and security of Muslim societies. The paper argues that a comprehensive approach to security is necessary to protect against this threat, which includes economic, political, and social measures. In conclusion, this paper provides a valuable contribution to the understanding of 5GW and its implications for Muslim societies. It emphasizes the importance of raising awareness about this issue in the light of Islamic teachings and developing proactive defense strategies to counter this threat. The paper offers practical recommendations for policymakers and military leaders on how to effectively confront the challenge of 5GW and ensure the security and stability of their societies.